Evaluation of antifatigue and antioxidant activities of the marine microalgae Isochrysis galbana in mice - Li, Wenjie (Food Sci Biotechnol, 2019)
The present work aimed to estimate the possible anti-fatigue effect and potential mechanism of Isochrysis galbana (IG) in mice. The anti-fatigue activity of IG (100, 200, and 400 mg/kg) was elucidated by a weight-loaded forced swimming test, and the potential mechanism was explored by determination of fatigue-related biochemical parameters. The results showed that pretreatment with IG significantly extended the exhaustive swimming time and increased the levels of liver glycogen, muscle glycogen and blood glucose in a dose-dependent manner. Besides, the increased levels of alanine aminotransferase, aspartate aminotransferase, blood lactic acid, lactic dehydrogenase, creatine kinase, and blood urea nitrogen by exhausted swimming, were dramatically attenuated by pretreatment with IG. Furthermore, supplementation with IG significantly enhanced the glutathione peroxidase and superoxide dismutase levels, while attenuated the level of malonaldehyde. Taken together, IG possessed appreciable efficacy to alleviate fatigue, and the mechanism might be associated with favorably modulating the process of energy consumption, metabolism, and attenuating oxidative stress injury.